THE ANTHROPOGENIC GRASSLANDS OF THE Securigero securidacae-Dasypyrion villosi IN CENTRAL MEDITERRANEAN AREAS: SYNECOLOGY, DISTRIBUTION AND SYNTAXONOMY - Fanfarillo, E.; Moretti, M.; Abbate, G. (Annali di Botanica, 2019)
The anthropogenic therophitic grasslands dominated by tall Poaceae of Italy were recently included in the alliance Securigero securidacae-Dasypyrion villosi (Chenopodietea). Similar vegetation types from Sicily, Sardinia, Albania, and Greece were hypothesized to pertain to this syntaxon. In this work, we performed multivariate analyses on 493 phytosociological relevés certainly or likely ascribable to the alliance, gathering personal unpublished data and those available from literature. Our results confirm that this vegetation type has its core distribution in peninsular Italy, with irradiations in Sardinia and the lower Po Valley. Except for one relevés, similar communities from the Balkans were not includable in the Securigero-Dasypyrion, as well as others from the Italian Peninsula and Sicily. Based on our results, we describe the Mediterranean sub-alliance Securigero securidacae-Dasypyrenion villosi (including six vegetation types) and its Submediterranean vicarious Hordeo murini-Anisanthenion diandrae (including three vegetation types). Three new associations are described.